2005
DOI: 10.1007/s00167-004-0591-8
|View full text |Cite
|
Sign up to set email alerts
|

Fear of re-injury: a hindrance for returning to sports after anterior cruciate ligament reconstruction

Abstract: Unrestricted participation in sports activities and return to the pre-injury level is often reported as an indicator of the success of ACL reconstruction. The athletes' choice not to return to their pre-injury level may depend on the knee function, but some times, social reasons or psychological hindrances such as fear of re-injury may influence their return to sports. The aim of this study was to investigate whether fear of re-injury due to movement is of significance for returning to previous level of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
600
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(672 citation statements)
references
References 15 publications
37
600
0
11
Order By: Relevance
“…Using the Tampa Scale of Kinesiophobia, Kvist et al identified fear of re-injury as a significant factor in patients who did not return to their pre-injury activity level compared to those who did [23]. In another study to investigate the role of psychological factors in patients recovering from ACL reconstruction, Langford et al [24] utilised the ACL Return to Sport after Injury scale (ACL-RSI scale) [49] and found that patients who returned to competitive sport at 12 months scored significantly higher (reflecting a more positive psychological response) at both six and 12 months than patients who did not return to competitive sport.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Tampa Scale of Kinesiophobia, Kvist et al identified fear of re-injury as a significant factor in patients who did not return to their pre-injury activity level compared to those who did [23]. In another study to investigate the role of psychological factors in patients recovering from ACL reconstruction, Langford et al [24] utilised the ACL Return to Sport after Injury scale (ACL-RSI scale) [49] and found that patients who returned to competitive sport at 12 months scored significantly higher (reflecting a more positive psychological response) at both six and 12 months than patients who did not return to competitive sport.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies of musculoskeletal pain have focused on fear-avoidance models, with data supporting the validity of these models for patients with low back Staerkle et al, 2004), knee (Granot and Ferber, 2005;Kvist et al, 2005), and cervical pain Nederhand et al, 2004). Fear-avoidance models have ambiguous support for patients with shoulder pain.…”
Section: Introductionmentioning
confidence: 99%
“…Yaralanma öncesi performanslarına dönen sporcularda hareket nedenli tekrar sakatlanma korkusu daha azdır (11). Depresyonda olan bireyler ise yaralanma sonrası yıl boyunca yaralanma öncesi düzeylere geri dönememekte ve yaralanmaya bağlı bu psikolojik tepkiler, fonksiyonel bozukluklara neden olabilmektedir (29).…”
Section: Discussionunclassified
“…Hareket ve aktivite korkusu kavramlarının yanı sıra, yeniden yaralanma korkusu kavramı da kinezyofobi ile aynı anlamda kullanılmaktadır. Kinezyofobi, spor yaralanması sonrasında rehabilitasyon veya tedavi sonuçlarını olumsuz yönde etkileyebilmektedir (11). Bunun aksine, spora geri dönüş motivasyonu ve algısı ise spora geri dönüşü pozitif yönde etkileyen psikolojik faktörlerdendir (12).…”
Section: Introductionunclassified